Differences in clinical and biological factors between patients with PFO-related stroke and patients with PFO and no cerebral vascular events - Badea, Raluca Ştefania; Ribigan, Athena Cristina; Grecu, Nicolae; Terecoasǎ, Elena; Antochi, Florina Anca; Bâldea Mihǎilǎ, Sorina; Tiu, Cristina; Popescu, Bogdan Ovidiu (Frontiers in Neurology, 2023)
Background While stroke is one of the most dissected topics in neurology, the primary prevention of PFO-related stroke in young patients is still an unaddressed subject. We present a study concerning clinical, demographic, and laboratory factors associated with stroke and transient ischemic attack in patients with patent foramen ovale (PFO), as well as comparing PFO-patients with and without cerebrovascular ischemic events (CVEs). Patients and methods Consecutive patients with PFO-associated CVEs were included in the study; control group was selected from patients with a PFO and no history of stroke. All participants underwent peripheral routine blood analyses, as well as, on treating physician's recommendations, screening for thrombophilia. Results Ninety-five patients with CVEs and 41 controls were included. Females had a significantly lower risk of CVEs than males (p = 0.04). PFO size was similar between patients and controls. Patients with CVEs had more often hypertension (n = 33, 34.7%), p = 0.007. No significant differences were found between the two groups with regard to routine laboratory tests and thrombophilia status. Hypertension and gender were identified in a binomial logistic regression model as independent predictors for CVEs, but with an area under the ROC curve of 0.531, suggesting a very poor level of discrimination between the two groups. Discussion and conclusions There is little difference between patients with PFO with and without CVEs in terms of PFO size and routine laboratory analyses. While still a controversial topic in the specialty literature, classic first-level thrombophilic mutations are not a risk factor for stroke in patients with PFO. Hypertension and male gender were identified as factors associated with a higher risk of stroke in the setting of PFO.